2009
DOI: 10.2320/matertrans.mra2008450
|View full text |Cite
|
Sign up to set email alerts
|

Interface-Dependent Mechanical Properties in MWNT-Filled Polycarbonate

Abstract: Static tensile tests, dynamic mechanical analysis as well as electron microscopy were used to characterize the macromechanical properties of MWNT-filled polycarbonate composites. Meanwhile the behavior of the nanotube/polymer interfaces was examined by changing nanotube contents and measuring electrical conductivity and dielectric spectroscopy. When the interface achieved the state of percolation (2 mass% MWNT), strain of fracture of MWNT-filled polycarbonate composites reached a peak of 9.3%, elastic modulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 22 publications
4
14
1
Order By: Relevance
“…A sharp decrease in the elastic modulus to levels similar to neat PC was, however, observed with addition of 5% w/w of MWNTs and steadily declined as the MWNTs compositions increased to 20% w/w. These results are in contradiction to the findings of Man et al and Chen et al, where a monotonical increase in the elastic modulus was observed with an increase in the MWNTs even though they found a decrease in tensile strength at high MWNTs concentrations. Their study found an improvement in the elastic modulus of approximately 20% higher than that of neat PC modulus at 4–5 wt%.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…A sharp decrease in the elastic modulus to levels similar to neat PC was, however, observed with addition of 5% w/w of MWNTs and steadily declined as the MWNTs compositions increased to 20% w/w. These results are in contradiction to the findings of Man et al and Chen et al, where a monotonical increase in the elastic modulus was observed with an increase in the MWNTs even though they found a decrease in tensile strength at high MWNTs concentrations. Their study found an improvement in the elastic modulus of approximately 20% higher than that of neat PC modulus at 4–5 wt%.…”
Section: Resultscontrasting
confidence: 99%
“…Investigation of PC/CNTs composite microstructures provided very good insights. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) studies were very informative and supported the relationship between MWNTs loading and the composite mechanical properties . However, contradicting results on the effects of composite homogeneity on electrical conductivity were observed.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This has been reported by many researchers. 22,24,35 This is also evident from images of failed MWCNT/PC composite samples ( Fig. 3(d)).…”
Section: 36mentioning
confidence: 55%
“…This type of a qualitative change in the stress-strain behavior with the composite becoming less ductile as CNT concentration increases has also been reported by other workers. 12,14,30 The reduced ductility of CNT/PC composites by addition of CNTs has also been reported for oriented melt-spun bers of CNT/PC composites 10,13 and for CNT/PC composites studied at cryogenic temperatures.…”
Section: Tensile Properties Of A-mwcnt/pc and F-mwcnt/pc Composite Lmsmentioning
confidence: 68%